Translation methods in the English to Indonesian version of the Japanese comic Wind Breaker: A Newmarkian approach - Khairunnisa Khairunnisa; Andri Purwanto (Journal Albion : Journal of English Literature, Language, and Culture, 2026)
Translation is a process of transferring meaning from one language to another. This study discusses the translation methods used in the Japanese comic titled Wind Breaker by Nii Satoru. Comic, as a popular form of work, has distinctive linguistic characteristics, such as the use of slang, greetings, and cultural expressions, which often pose challenges for translators. This study aims to identify the translation methods used in the translated comic Wind Breaker and analyze the reasons for their selection. The research method used is descriptive qualitative, with data sources in the form of dialogues in the comic Wind Breaker chapters 179-181, which have been translated into English. The analysis was based on the translation method theory proposed by (Newmark, 1998), such as word-for-word, literal, semantic, and others. The results showed that the most dominant translation methods and techniques used in this comic are communicative (27,78%), literal (11,11%), and modulation (25%).